A MODEL FOR TEACHING READING COMPREHENSION AT JUNIOR HIGH SCHOOLS - Ermita, Ermita (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
This article reveals an alternative model for teaching reading comprehension at junior high school. This model is a combination of ‘interactive mdel’ and ‘cognitive mode’. The discussion covers two levels of  reading comprehension: the lowest level (literal comprehension) and the highest level (evaluation and appreciation). There are four trainings given dealing  with these levels; (1) literal comprehension training, (2) inferential comprehension training, (3) evaluation training, and (4) appreciation training. The last coverage of this article is about the advantages of proposed model. This model is designed and hopefully will be useful for language teachers who are training or planning to train learners to have good reading comprehension strategies, particularly at junior high school .